"Could You Help Me Die?": On the Ethics of Researcher-Participant Relationship and the Limitations of Qualitative Research. (31st May 2022) - Sperling, Daniel
Qualitative research is beneficial for researchers and society, and even for the participants themselves. Yet, end-of-life qualitative research also entails unique challenges given the sensitive topic and questions relayed to the participants, and the participants' requests of the researchers. This paper was written following ethical issues that arose while conducting in-depth interviews with Israeli members of the Swiss Dignitas Organization in 2019. The interviews enabled participants to air their thoughts on assisted suicide and gather information about related plans that were not available to the public due to various issues. Yet, during these interviews, I also found myself dealing with significant ethical dilemmas that I had not previously encountered, such as participants asking me to lie for them, or accompany them to Switzerland to fulfil their wishes. While the interviews served as a safe environment in which the participants could air their thoughts on the topic, they led me to reexamine the ethical limitations of qualitative research and the researcher-participant relationship (within and outside the research context). By analyzing three of these interviews, I attempted to answer the following research question: What do the ethics of qualitative research entail with regards to researcher-participant boundaries, as established in sensitive situations and that involve vulnerable populations in end-of-life situations? The analysis was conducted in line with the ethical mindfulness framework and combined theoretical analysis of the literature. My analysis indicates that while qualitative research encourages the establishing of a researcher-participant relationship through trust and rapport – especially on sensitive topics that involve vulnerable populations – the researcher must also ensure both participant and researcher safety, by establishing and maintaining boundaries, even post-research. Introspective ethical inquiry, triggered by participants, requires the researcher to be vulnerable, potentially resulting in emotional discomfort. It also mandates re-engaging with the participants on ethical meanings that stem from this process.